OP0271 Differential regulatory functions of HIF-1α and HIF-2α during angiogenesis of human microvascular endothelial cells (HMECS). (23rd January 2014) - Hahne, M.; Luetkecosmann, S.; Tran, C.L.; Strehl, C.; Fangradt, M.; Jakstadt, M.; Duda, G.; Hoff, P.; Gaber, T.; Burmester, G.-R.; Buttgereit, F.
Abstract : Background: Hypoxia and angiogenesis are features of inflamed and injured tissues. The transcription factors Hypoxia inducible factor (HIF)-1α and (HIF)-2α control cellular metabolic response to decreased oxygen tension thereby promoting angiogenesis and having implications on the pathogenesis of RA. Objectives: We focused on the effects of HIF-1α and HIF-2α on angiogenesis and developed a human microvascular endothelial cells (HMEC) lentiviral based knockdown system for both transcription factors allowing us to analyze angiogenesis of HMECs under hypoxia in the absence of HIF-1α or HIF-2α, respectively. Methods: Specific knockdown of HIF-1α or HIF-2α was achieved using lentiviral-based shRNA technology. The reduction of HIF-1α or HIF-2α was confirmed on transcriptional and translational level by realtime RT-PCR and Western blot. Angiogenesis of transduced HMECs in comparison to scrambled cells was studied by investigating both tubuli and node formation under hypoxia (<1% O2 ). Expression of hypoxia driven genes HIF1A, HIF2A, VEGFA and IL8 was quantified by realtime RT-PCR. Multiplex suspension array technology was used to measure the concentrations of secreted VEGF and IL8. Results: The successful knockdown of HIF-1α and HIF-2α was confirmed by demonstrating considerably reduced gene expression levels of HIF1A and HIF2A by up to 71% (p=0.0222) under normoxic and hypoxic conditions. As a consequence, strongly reduced HIF-1α and HIF-2α protein levels were detected by Western blot. Targeting of HIF-1α led to a significantly decreased node formation (1.6-fold change under hypoxia, p=0.0067) with similar effects by trend on tubuli formation. The HIF-2α knockdown also led to a significantly decreased tubuli formation (1.7-fold change, p=0.0444) with similar effects by trend on node formation. Furthermore, HIF-1α targeted cells did not show any significant decrease in the gene expressions of VEGFA and IL8 but surprisingly raised cytokine levels of IL8 under hypoxia (1.4-fold change, p=0.021) compared to the control. In contrast, targeting of HIF-2α gave rise to reduced levels of secreted VEGF and IL8 with a significant suppression of IL8 gene expression under normoxia (2.1-fold change, p=0.0101). Conclusions: Our findings show essential and overlapping functions of HIF-1α and HIF-2α with regard to their regulatory potential of angiogenesis in HMECs. Both transcription factors have the same impact on VEGF but differ in their effects on IL8 expression. These findings provide new insights into basic principles of angiogenesis in inflamed tissues and are therefore considered to be of clinical importance. Disclosure of Interest: None Declared